EARLY-STAGE TESTICULAR CANCER MANAGEMENT REFERRING TO EUROPEAN ASSOCIATION OF UROLOGY (EAU) GUIDELINES: A SURVEY IN INDONESIA - Zen Ary Prasetyo; Seputra, Kurnia Penta; Rainy Umbas; Besut Daryanto (Indonesian Journal of Urology, 2023)
Objective: This study aimed to determine the management of early-stage testicular cancer among urologists in Indonesia by using a survey. Material & Methods: This research was a descriptive-analytic study using a survey method through a Google-forms questionnaire distributed to urologists throughout Indonesia who were willing to participate. Data were collected from September 1 to 30, 2021. Results: Of the total respondents, 15 (14.2%) respondents were consultant urologic oncologists, and 90 (85.71%) respondents were non-consultant urologists or consultant urologists non-oncology. There was no difference in the treatment given by consultant uro-oncologists and non-consultant urologists/consultant urologists non-oncology in the management of surveillance of stage IA-IB seminoma (66.7% vs. 55.6%, p-value = 0.207), chemotherapy of stage IIA-IIB seminoma (100.0% vs. 90.0%, p-value = 0.080), surveillance of stage I non-seminoma cancers (46.7% vs. 41.1%, p-value = 0.304), and chemotherapy of stage IIA and IIB non-seminoma cancers (80% vs. 91.1%, p-value = 0.193). Conclusion: In general, as many as 84.4% of oncology consultant urologists and 83.7% of non-consultant urologists/consultant urologists non-oncology have performed initial diagnostic examinations, treatment, and follow-up following testicular cancer management guidelines according to the European Association of Urology 2021.